Types of Flouting Maxim in “No Hard Feelings” Movie - Putu Regina Yohana Pratiwi; Putu Devi Maharani (Program Studi Magister Ilmu Linguistik Universitas Warmadewa, 2024)
TThis study analyzes the types of flouting maxim conveyed by the characters in the movie No Hard Feelings. No Hard Feelings is a movie about a desperate woman who almost loses her house and decides to date a wealthy couple’s son to solve the problem. Flouting maxim occurs when the participant disobeys Grice’s conversational maxims in a conversation. This study used the theory from Grice (1975) concerning the cooperative principle to discover the types of flouting maxims. The types of flouting maxims were collected by qualitative method through an observation of the utterances done by the characters in the movie. This study also used theory from Halliday (1989) to analyze the context of the situation based on the conversation. The result of this study revealed that there are 4 types of flouting maxim found in 25 data, namely flouting maxim of quantity, flouting maxim of quality, flouting maxim of manner, and flouting maxim of relevance. The highest flouting maxim in the No Hard Feeling movie is the flouting maxim of quantity because most of the characters added more or less unnecessary information to their statement. The main character disregarded most of the maxim of quantity. The main character flouted the maxim by providing excessive detail to stress the audience hence the character wanted to control the conversation to achieve her goal as a main character. This study focuses on demonstrating the dialogues that were considered flouts in the movie and correlates the flouts with linguistic theory.